Some thoughts on thermodynamics of internal variables - Valanis, K.C. (Archives of Mechanics, 1997)
The thoughts and ideas expressed here are meant to address the remarks and comments that were made by various speakers during the 31st Polish Solid Mechanics Conference. It was felt at the time that a complete picture of the theory on thermodynamics of internal variables appeared to be lacking in some issues that are of critical interest technically as well as historically. These comments are meant to address these issues.